Design of systems for integrated processing of dairy raw materials in the cheese industry - Yatskov, Mykola; Korchyk, Natalia; Besediuk, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2021)
For the functioning of integrated systems for processing dairy raw materials in the cheesemaking industry, it is proposed to consider the basic concepts of synthesis of production systems. In order to implement the concept of waste minimization, it is proposed to separate the industrial wastewater into flows based on the concentration and values of the main parameters, as well as to protect the cheese whey from entering the water treatment facilities and direct it for disposal. The possibilities of implementing the concepts of deep raw materials processing into a target product have been analyzed, as well as the full utilization of raw and auxiliary materials. To this end, an experimental study was performed on the extraction of protein clots and adjusting the buffer capacity of infant dairy products using cheese whey. The study results indicate the insufficient effect of extracting the protein clot from whey (5–50 %) by combining the thermal and chemical processes. It was established that the redox conditions of the medium, in terms of the Eh indicator, can significantly affect the results, in close connection with the pH parameter and the estimated value of rH2. It was found that the optimal conditions for the functioning of lactic acid microflora in the production of soft cheeses can be ensured by adjusting the Eh indicator through the introduction of whey of pH=4.4–4.6 units, Eh≤–0.1 V. Whey is introduced at the stage of dairy raw material fermentation, which creates optimal conditions for the formation of a clot until reaching rH2 in the range from −5 to –7, and increases the product output by 1.5–7 %. The results of the experimental study indicate the high potential of using whey desalinated by ion exchange in order to reduce the buffer capacity in terms of acidity and adjust the redox conditions for infant milk mixtures until achieving rH2=15.5–15.9. The research reported in this paper could be the basis for the further development of systems for the integrated processing of dairy raw materials in the cheesemaking industry